Respostas

  • Usuário do Brainly
2013-01-08T15:38:45-02:00

O 1^{\circ} termo é -15 e a razão é 6.

Desta maneira, tém-se:

1^{\circ} termo = -15

2^{\circ} termo = -15 + 6 = -9

3^{\circ} termo = -9 + 6 = -3

4^{\circ} termo = -3 + 6 = 3

5^{\circ} termo = 3 + 6 = 9

6^{\circ} termo = 9 + 6 = 15

...


\text{n}^{\circ} termo = (\text{n}-1)+6

Desse modo, obtemos a P.A: \{-15, -9, -3, 3, 9, 15\}

  • Usuário do Brainly
2013-01-08T17:08:04-02:00

Numa PA,cada termo é o anterior mais a razão

 

Então:


1o termo = - 15

2o termo = - 15 + 6 = - 9

3o termo = - 9 + 6 = - 3

4o termo = - 3 + 6 = 3

5o termo = 3 + 6 = 9

6o termo = 9 + 6 = 15

 

PA = - 15, - 9, -3, 3, 9, 15

 

Ajudou?